Securing your Internet connection a sequel. - Rabinovitch, E.
This author discusses the problem of Internet security. He draws some parallels between spammers trying to trick victims to opt out of their e-mail list in order to obtain information on valid e-mail addresses with so-called social engineering techniques used by security perpetrators. The term social engineering is typically used to describe a human-interactive (the emphasis is on the word human as opposed to computer-based) process that tricks people into violating security policies and procedures to get unauthorized access to protected information exposing security vulnerabilities. The best way to deal with social engineering threats is through creating and enforcing strict security procedures through education and training
Keywords: Internet connection security; E-mail address; Education; Security policies; Social engineering techniques; Spammers; Training; Unauthorized information access